Physical and chemical oceanography during SONNE cruise SO277 from towed Video-CTD03, off Malta - Mark Schmidt (PANGAEA, 2025)
Data set presents water column and bottom water oceanographic parameters recorded with a video-guided Water Sampler Rosette/CTD system during SO277 cruise off Malta (Berndt et al., 2021). The Video-CTD (VCTD) recorded water-column hydrocast data and towed CTD data in bottom view mode about 1.5 m above seafloor. The data was used to identify fluid release structures (i.e. pockmarks) at the seafloor and physical/chemical anomalies in bottom water related to fluid/gas seepage. Any measured anomaly will be correlated to subsurface geophysical structures (e.g. Offshore freshened Groundwater, OFG).